THE EFFECT OF ELECTRODE COATING FROM BISPHENOL-A-POLYCARBONATE CD-R WASTE FOR HYDROGEN PRODUCTION - Sulaiman, Abdul Mudjib; Mas'ud, Sifa'ul; Daroini, Ahmad Najih; Purnami, Purnami (International Journal of Mechanical Engineering Technologies and Applications, 2023)
Water electrolysis is a method that utilizes direct electric current to decompose water into O2 and H2. The productivity of hydrogen produced in the electrolysis of water is low. One of the main reasons for the low electrolysis efficiency of water is the resistance of the electrode material. The electrode that is often used in the electrolysis of water is a graphite electrode. The coating on graphite electrodes can be a solution to minimize material degradation at the electrodes. With the condition that the coating material is able to slow down the damage to graphite electrodes and is a good electrical conductor. In this study, we used polycarbonate material as a material for coating the electrodes. The polycarbonate material that will be used is obtained from electrical waste, namely CD-R. The polycarbonate was separated mechanically and then ground to a powder with a size of 400 m. Polycarbonate powder will be coated on the cathode surface by the thermal coating method. Polycarbonate contains Bisphenol A compound which has an aromatic ring. The presence of a magnetic field caused by the delocalization of electrons in aromatic compounds will affect the hydrogen bonding in water. The positively charged surface charge of Bisphenol-A-Polycarbonate is able to reduce the acidity of the solution and accelerate the decomposition reactions of H2 and O2 by the water electrolysis method. Bisphenol-A-Polycarbonate coating is a good inhibitor for graphite electrodes. Coated graphite electrodes have a lower corrosion rate than pure or uncoated graphite electrodes. The layer inhibits the degradation of the material caused by electrochemical events during the water electrolysis process. Bisphenol-A-Polycarbonate (BPA) layer, which acts as an inhibitor and a catalyst simultaneously during the water electrolysis reaction, causes hydrogen production to increase.